2012
DOI: 10.1371/journal.pone.0037996
|View full text |Cite
|
Sign up to set email alerts
|

External Urethral Sphincter Pressure Measurement: An Accurate Method for the Diagnosis of Detrusor External Sphincter Dyssynergia?

Abstract: BackgroundCombined pelvic floor electromyography (EMG) and videocystourethrography (VCUG) during urodynamic investigation are the most acceptable and widely agreed methods for diagnosing detrusor external sphincter dyssynergia (DESD). Theoretically, external urethral sphincter pressure (EUSP) measurement would provide enough information for the diagnosis of DESD and could simplify the urodynamic investigation replacing combined pelvic floor EMG and VCUG. Thus, we evaluated the diagnostic accuracy of EUSP measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The implantation‐induced tissue alterations need to be considered when bladder‐specific processes are assessed. In humans, combined pelvic floor EMG and videocystourethrography (VCUG) during urodynamic investigation are the most acceptable and widely agreed methods for diagnosis of DSD , especially considering that both detrusor internal and external sphincter dyssynergia can be investigated. VCUG is not yet available in rats but we are working on some additional improvements and in the optimal case a video‐urodynamic assessment could be established.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation‐induced tissue alterations need to be considered when bladder‐specific processes are assessed. In humans, combined pelvic floor EMG and videocystourethrography (VCUG) during urodynamic investigation are the most acceptable and widely agreed methods for diagnosis of DSD , especially considering that both detrusor internal and external sphincter dyssynergia can be investigated. VCUG is not yet available in rats but we are working on some additional improvements and in the optimal case a video‐urodynamic assessment could be established.…”
Section: Discussionmentioning
confidence: 99%
“…Detrusor-sphincter dyssynergia was defined as 1) detrusor contraction concurrent with involuntary contraction of the urethral and/or periurethral striated muscle 6,7 on pelvic floor electromyography in the absence of the Valsalva or Cred e maneuver and/or 2) a dilated posterior urethra obstructed by the external urethral sphincter on fluoroscopy during videourodynamics as described previously. 12 Patients with asymptomatic bacteriuria were not treated and no antibiotic prophylaxis was administered for UDI.…”
Section: Neurourological Evaluationmentioning
confidence: 99%
“…In 2001, Sakakibara et al [13] looked at the reduction in urethral sphincter pressure during voiding for patients with DSD and found that urethral pressure decreased by an average of 6.4 and 5.0 cm H 2 O for men and women, respectively with DSD compared to 39 and 53 for those without [13]. Taking this information, Suzuki et al [8] examined the utility of urethral pressure as an alternative to combined EMG/VCUG for measuring DSD. They defined urethral pressure DSD as any increase, maintenance, or decrease <10 cm H 2 O of urethral pressure during the voiding phase.…”
Section: Discussionmentioning
confidence: 99%
“…Urethral sphincter pressure measurements during urodynamics may offer an alternative or supplemental method for diagnosing DSD and yield measurement data that can be used to better characterize physiology [6]. Currently, there are few published techniques for using urethral pressure measurements to categorize DSD and these reports have yielded inconsistent data [7,8]. Consequently, using urethral pressures to diagnose DSD is currently considered experimental by the International Continence Society (ICS) [6].…”
Section: Introductionmentioning
confidence: 99%